2004
DOI: 10.1159/000076236
|View full text |Cite
|
Sign up to set email alerts
|

Can Optimal Primary Cytoreduction Be Predicted in Advanced Stage Epithelial Ovarian Cancer? Role of Preoperative Serum CA-125 Level

Abstract: The aim of this study was to determine the ability of preoperative serum CA-125 levels to predict optimal cytoreduction in patients with stage III epithelial ovarian cancer. A retrospective review was made of the records of 40 patients with FIGO stage III ovarian carcinoma who underwent primary cytoreductive surgery. A receiver operating characteristic (ROC) curve was used to determine the most useful CA-125 level in predicting optimal versus suboptimal tumour cytoreduction. Twenty-two (55%) patients were opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 16 publications
0
20
1
2
Order By: Relevance
“…Recognition that all patients undergoing initial cytoreduction surgery cannot be optimally cytoreduced has led to the use of diagnostic imaging techniques, serum biomarkers, and diagnostic laparoscopic procedures to identify which patients might not be suitable for undergoing conventional therapy [3,[29][30][31][32][33][34][35][36].…”
Section: Which Patients Might Best Benefi T From Receiving Neoadjuvanmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition that all patients undergoing initial cytoreduction surgery cannot be optimally cytoreduced has led to the use of diagnostic imaging techniques, serum biomarkers, and diagnostic laparoscopic procedures to identify which patients might not be suitable for undergoing conventional therapy [3,[29][30][31][32][33][34][35][36].…”
Section: Which Patients Might Best Benefi T From Receiving Neoadjuvanmentioning
confidence: 99%
“…Using serum CA-125 levels as objective means of establishing which patients cannot be optimally surgically cytoreduced has produced confl icting results in the literature [33][34][35][36].…”
Section: Which Patients Might Best Benefi T From Receiving Neoadjuvanmentioning
confidence: 99%
“…However, after the year 2000, with the change in practice to ultra-radical cytoreductive surgery, the CA125 level was no longer shown to be predictive of the ability to optimally cytoreduce patients. This has been supported by several other studies [42][43][44]. However, recently De Jong et al [45] reported a normogram that predicted tumor resectability based on serum CA125 and albumin levels.…”
Section: Ca125mentioning
confidence: 61%
“…14 In many studies it has also been shown that the preoperative level of CA125 can serve as a predictor of optimal tumor cytoreduction in advanced ovarian cancer. [15][16][17][18][19] In these studies high preoperative CA125 serum levels were associated with decreased likelihood of achieving an optimal cytoreduction, although the threshold cutoff levels differed in them. On the other hand, in other studies preoperative serum CA125 level was not found to be a reliable predictor of optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 91%